Design of a Website-Based Field Rental Information System for Rajawali Futsal - Bachtiar, Galuh; Riyanto (Yayasan Kita Menulis, 2025)
This study aims to design and develop a field rental information system for Rajawali Futsal, which has been relying on manual methods for administration and data recording. The manual method often leads to data management errors and inefficiencies in customer service. One of the main issues identified is the inconvenience for customers who need to visit the location in person to make a reservation, which causes time constraints and discomfort. Additionally, the manual handling of financial reports makes it difficult for the management to obtain accurate and timely reports. To address these issues, this study adopts the Waterfall system design methodology, which includes the stages of requirements analysis, system design, implementation, and testing. The system designed in this research aims to improve the efficiency and accuracy of the field rental process and data management. With the website-based system, customers can make field reservations online, choose available times and fields, and make payments without having to visit the location. Additionally, the system includes a financial reporting feature that allows the management to monitor and evaluate transactions in real-time and in a more structured manner. The results of this study show that the implementation of a website-based information system can improve the ease of field rental processes, reduce data recording errors, and speed up the management of financial data. With this integrated system, it is expected that customer satisfaction will increase and the operational management of Rajawali Futsal will become more efficient and effective.